MODERNISASI PESANTREN - M. Thoyyib (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
Abstract: Modernity as a new value that come with Western industrialization, causing various responses from each element of the nation not except Pesantren. Pesantren as a subculture has its own value system and that became the standard in response to modernity. This is what made the basis of criticism Nurcholis Madjid, that if schools do not want to accept modernity, then what happens is the socio-cultural lag. Pesantren is removed from the life in modern life. Boarding schools must develop a learning system by integrating existing systems current with the Madrasi system. In addition, teacher competence, facilities and instructional media should also be revised and adjusted to the current global conditions. Boarding schools have a strong standard stored value and the background for their renewal, the default value is the value of Ahl al-Sunnah WA al-Jama, with operational rules al-Muhafadah 'ala al-Qadeem al-Salih al-Akhdzu wa bi al -Jadid al-Aslah.